Health Supervision Visits among SSI-Eligible Children in the D.C. Medicaid Program: A Comparison of Enrollees in Fee-for-Service and Partially Capitated Managed Care - Jean M. Mitchell; Darrell J. Gaskin; Chahira Kozma (SAGE Publishing, 2008)
Managed care plans that involve some form of capitation may have adverse effects on children with special health care needs because the financial incentives to control costs may result in under-treatment and restrict access to expensive services and specialty providers. Proponents highlight the advantages of a managed care model, including case management and coordination of services. In light of this debate, only a few state Medicaid programs have implemented a managed care option for children with special health care needs. This study evaluates the effects of plan choice (partially capitated managed care versus fee-for-service) on whether children with disabilities eligible for Supplemental Security Income (SSI) and enrolled in the District of Columbia's Medicaid program are in compliance with the guidelines for health supervision visits established by the American Academy of Pediatrics (AAP). Our findings, based on five years of claims data, show that SSI-eligible children with disabilities enrolled in a partially capitated managed care plan are significantly more likely to be in compliance with the AAP guidelines for health supervision visits compared to their fee-for-service counterparts. Moreover, we find that selection due to unobservable characteristics does not significantly bias the estimated program effects.